DEVELOPMENT OF AN EMPLOYABILITY MEASUREMENT SCALE FOR COOPERATIVE EDUCATION STUDENTS: EXPLORATORY FACTOR ANALYSIS - Soe Oo, Paing; Pramot, Phrakhrupaladatthachariyanukit; Bhukrongna, Watanyu; Bamrungsin, Phanommas (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 5 No 2 (2568): พฤษภาคม – สิงหาคม 2568, 2025)
This study aimed 1) to developed and validated the Employability Measure Scale for Thai Undergraduates (EMS-TU), and 2) to identify the factors that influence co-op student employability. The sample consisted of 96 undergraduate students from public autonomous universities in Thailand selected through stratified random sampling technique. The research instrument used in this study was survey questionnaire. The statistics used for data analysis included 1) the Index of Item-Objective Congruence (IOC) to examine content validity of the scale, 2) Cronbach’s alpha was used to measure internal consistency reliability, and 3) Exploratory factor analysis (EFA) was employed to investigate the potential underlying factor structure of observed variables.            The results of this study were as followings: 1) IOC scores indicated strong content validity with the values ranging between 0.80 and 1.00, Cronbach’s alpha value 0.889 confirmed high reliability, EFA result demonstrated a five-factor version of 23 items with a range of factor loadings from 0.699 to 0.930. 2) The EMS-TU comprises five constructs: English language proficiency, career decision self-efficacy, university commitment, university support, and internship quality. The scale demonstrated strong construct validity and internal consistency, can be used to assess and monitor their students’ employability skills for students in higher education institutions in Thailand. The finding of this study informs curriculum development, guide skill enhancement initiatives, and ultimately support the alignment of graduate outcomes with labor market expectations.